Prototype of Power Sharing Automation System in 3 Phase Power Source Based on Internet of Things - Ali Mahfud Roziqin; Indah Sulistiyowati; Shazana Dhiya Ayuni; Syamsudduha Syahrorini (Procedia of Engineering and Life Science, 2022)
In companies or goods storage places, to see the value of the load current in the RST phase, we still use Clamp Ampere and in doing power distribution using manual work by moving the load on the RST phase from one MCB to another MCB until it is evenly distributed so that the process takes time. In this study, the method of observation and literature study was used to implement the ACS712 sensor as a current sensor on a prototype power splitter automation system on a 3-phase power source based on the internet of things as a tool in the form of a prototype with 3 200 watt incandescent lamp loads that can be operated with a finger remotely using android smartphone to help users so that power distribution is not manually and can be automatically evenly distributed in each RST phase. The results of automatic power sharing with 3 200 watt incandescent lamp loads, the first load is automatically turned on using the R phase with a current value of 0.8 Ampere, then the second load is turned on automatically using the S phase with a current value of 0.8 Ampere and the third load turned on automatically using phase T with a current value of 0.8 Ampere. The difference between the readings of the current value between the Clamp Ampere and the blynk is 0.03-0.08 Ampere and to find out the current value in each phase can be seen in the blynk application.